Respuesta :
(3,6)(-2,1)
slope = (1 - 6) / (-2 - 3) = -5/-5 = 1
point slope form : y - y1 = m(x - x1)
slope(m) = 1
(3,6)....x1 = 3 and y1 = 6
now we sub
y - 6 = 1(x - 3) <===
slope = (1 - 6) / (-2 - 3) = -5/-5 = 1
point slope form : y - y1 = m(x - x1)
slope(m) = 1
(3,6)....x1 = 3 and y1 = 6
now we sub
y - 6 = 1(x - 3) <===
Find the slope first.
So
slope (m) = y2-y1/x2-x1
m=1-6/-2-3
m=-5/-5
m=1
The slope is 1
The equation for point slope form is
y-y1=m(x-x1)
y-6=1(x-3)
Therefore the equation in point slope form of the line passing through the points is y-6=1(x-3)
So
slope (m) = y2-y1/x2-x1
m=1-6/-2-3
m=-5/-5
m=1
The slope is 1
The equation for point slope form is
y-y1=m(x-x1)
y-6=1(x-3)
Therefore the equation in point slope form of the line passing through the points is y-6=1(x-3)